The behavior of a foundation transversally loaded at the top over highly porous and collapsible soil (2016)
In geotechnical engineering, the use of caisson foundations transversally loaded at the top is common. This type of foundation is frequently used on high-porosity and collapsible soils, which are common in many regions in Brazil. Because of the limited information available in the literature, two loading tests were performed with transversal loading in a caisson built at full scale (0.8 m diameter, 9.0 m depth, 1.6 m base diameter). A load test was performed with the soil in its natural humidity condition, and another load test was performed after the previous soil flooding. Load vs horizontal displacement curves and the horizontal direction coefficient of the soil were obtained. The results permitted the verification of the applicability of behavior-predicting theoretical formulae in addition to the proposal of parameters for use on the studied soil. Before executing the load tests, laboratory and in-situ tests were performed to investigate the local subsoil.